Exploring a novel ceramic (Ti, W)3SiC2 for interconnect of intermediate temperature solid oxide fuel cell. (12th April 2018) - Zheng, Lili; Hua, Qingsong; Li, Xichao; Li, Meishuan; Qian, Yuhai; Xu, Jingjun; Dai, Zuoqiang; Zhang, Hongxin; Zhang, Tiezhu; Wu, Junwei
Abstract: A solid solution (Ti, W)3 SiC2 possessing good oxidation resistance and low area-specific resistance (ASR) after oxidation has been synthesized by an in-situ hot pressing process. The oxidation rate constant at 800 °C in air is 6.29 × 10 −14 g 2 cm −4 s −1 for (Ti, W)3 SiC2 . The formed single-layer oxide is composed of W doped rutile TiO2 and amorphous SiO2 . SiO2 is evenly inlaid in the communicative body frame of TiO2 . W doped in TiO2 mainly exists as W 6+ . W doping not only hinders the outward diffusion of Ti by decreasing the concentration of native Ti interstitials in TiO2, but also restrains the inward diffusion of oxygen by decreasing the concentration of O vacancies. Furthermore, W dopant in TiO2 enhances the electrical conductivity of TiO2 by increasing the concentration of semi-free electron. Therefore, the low ASR of (Ti, W)3 SiC2 after oxidation owes to high electrical conductivity of TiO2 as well as the reduced thickness of oxide scale. All the results render (Ti1-x Wx )3 SiC2 promising as interconnects for the intermediate temperature solid oxide fuel cell. Highlights: A novel ceramic (Ti0.95 W0.05 )3 SiC2 is explored for interconnect of IT-SOFC. This ceramic possesses good oxidation resistance and electrical conductivity. The single oxide layer is composed of W 6+ doped TiO2 and amorphous SiO2 . Amorphous SiO2 evenly inlaid in communicative r-TiO2 body frame in the scale. W doping decreases [ V o ] and [ T i i 4 + ] in TiO2 to decrease oxidation rate and ASR.